Determinants of Impulsive Buying Behavior: An Empirical Analysis of Consumers’ Purchase Intentions for Offline Beauty Products - Tanveer, Tayyaba; Kazmi, Syeda Quratulain; Rahman, Mustaghis Ur (Nurture, 2022)
Purpose: The purpose of this research is to identify the underlying factors of impulsive buying behavior that would impact consumers’ buying behavior and eventually their purchase intentions. Methodology: This research is based on the philosophy of positivism and employs a quantitative examination. In order to reach to our target market, we have used convenience sampling (non-probability sampling) and tried to gather the data in the original shopping environment i.e. a survey in shopping malls. A sample of 400 was gathered and analyzed. The SPSS version 20 is used for data analysis. Findings: Results of this study show that a consumer’s mood has a significant impact on buying as it can trigger impulse behavior in consumers. Person situations can also influence impulse buying for example time, money and the fear of missing out can all trigger impulse buying. Store layout can also trigger that unplanned purchase which means store lighting, the music of the store and ambiance may affect the purchasing. Product promotion has an impact on spontaneous purchase which indicates that free coupons, discounts and free delivery are offered to attract the customer to a sudden purchase. Product design, packaging, color and labeling indicate a positive and significant impact on impulse buying. However, materialism indicates an insignificant impact on impulse buying. Contribution to literature: This research is positively contributing to or suggesting that practitioners or sellers better understand the intrinsic factors influencing customers ’purchase intentions in the cosmetic industry.